2022
DOI: 10.3390/cancers14092142
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Contrasts IL-6 Pro-Growth Effects and Promotes Autophagy-Mediated Cancer Cell Dormancy in 3D Ovarian Cancer: Role of miR-1305 and of Its Target ARH-I

Abstract: Tumor dormancy is the extended period during which patients are asymptomatic before recurrence, and it represents a difficult phenomenon to target pharmacologically. The relapse of tumors, for instance arising from the interruption of dormant metastases, is frequently observed in ovarian cancer patients and determines poor survival. Inflammatory cytokines present in the tumor microenvironment likely contribute to such events. Cancer cell dormancy and autophagy are interconnected at the molecular level through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…The high glucose uptake induced by IL-6 associated with increased levels of ROS (red signal), was more evident in OVCAR3 cells. In a separate study, we showed that under this condition cell viability is however not affected [ 17 ]. MB contrasted the production of anion superoxide induced by IL-6, confirming that these ROS arose from overwhelming the respiratory chain caused by increased glycolytic flux ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high glucose uptake induced by IL-6 associated with increased levels of ROS (red signal), was more evident in OVCAR3 cells. In a separate study, we showed that under this condition cell viability is however not affected [ 17 ]. MB contrasted the production of anion superoxide induced by IL-6, confirming that these ROS arose from overwhelming the respiratory chain caused by increased glycolytic flux ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…In the last years, the anti-cancer properties of natural compounds, along with their low toxic side effects, have attracted the interest of researchers [ 39 ]. Our group extensively reported the beneficial effects of the nutraceutical resveratrol (RV) that acts as a potent autophagy inducer, caloric restriction mimetic, and is capable to modulate the epigenome of the cancer cells, the secretion of cytokines and mitogenic factors, and to limit angiogenesis, immune suppression, and the activation of cancer-associated fibroblasts [ 16 , 17 , 18 , 19 , 20 , 27 , 40 ]. In the present work, we found that RV counteracts ovarian cancer cell migration by mimicking the phenotypic changes observed in glucose deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of autophagy by RSV has been reported in many in vitro studies, and here we have confirmed such effect in a syngeneic mouse model of lung cancer. Remarkably, we have previously demonstrated that RSV-induced autophagy can oppose ovarian cancer cell migration and proliferation while supporting a dormant phenotype [ 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In normal cellular homeostasis of cardiomyocytes, H19 downregulates DIRAS3 (distinct subgroup of the Ras family member 3) expression through the recruitment of EZH2 to induce H3K27me3 methylation on the DIRAS3 promoter [ 188 ]. DIRAS3 inhibits cell proliferation and promotes autophagy-mediated cell dormancy [ 224 ]. Downregulation of H19 observed in DCM leads to the depression of DIRAS3 and the resultant inhibition of Akt-signaling pathway and autophagy of cardiomyocytes, promoting DCM [ 188 ].…”
Section: Lncrnas In Human Diseasesmentioning
confidence: 99%